Board gender diversity, CEO overconfidence, and ESG risk in mining companies - I Wayan Kartana; Ni Kadek Ayu Prawita Sari; Anak Agung Bagus Amlayasa; I Gusti Ayu Ratih Permata Dewi; Sanju Kumar Singh (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Environmental, Social, and Governance (ESG) risk is critical to business resilience, yet it may be intensified by executive cognitive biases. This study examines the effect of CEO overconfidence on ESG risk and investigates board gender diversity as a moderating mechanism. CEO overconfidence is proxied by capital expenditure intensity (CAPEX), overinvestment, and the debt-to-equity ratio (DER). Using an explanatory quantitative design, this study analyzes 34 mining companies listed on the Indonesia Stock Exchange from 2021 to 2024. The data were analyzed using panel data regression with the Random Effect Model and Moderated Regression Analysis. The results indicate that, among the three proxies, only CAPEX significantly increases ESG risk, while the overinvestment and DER hypotheses are not supported. However, board gender diversity does not mitigate the effect of CEO overconfidence on ESG risk. Descriptive statistics further show that overinvestment and DER have mean values of 0.2500 and 0.0034, respectively, suggesting more conservative or underconfident CEO behavior. An interesting finding is that women’s representation on the board is only 9%, indicating that their presence remains limited in strategic risk-taking decisions. These findings indicate that mining companies should strengthen gender-responsive governance by increasing women’s representation in top leadership to enhance sustainability and reduce excessive executive risk-taking. These findings also imply that IDX, OJK, investors, and credit rating agencies should move beyond symbolic gender diversity by encouraging a critical mass of female directors and integrating board composition and CEO behavioral profiles into ESG risk assessment to support sustainable corporate governance.